Nanoscale subcellular architecture revealed by multicolor 3D salvaged fluorescence imaging - Zhang, Yongdeng; Schroeder, Lena K; Lessard, Mark D; Kidd, Phylicia; Chung, Jeeyun; Song, Yuanbin; Benedetti, Lorena; Li, Yiming; Ries, Jonas; De Camilli, Pietro; Rothman, James E; Baddeley, David; et al. (bioRxiv, 2019)
Combining the molecular specificity of fluorescent probes with three-dimensional (3D) imaging at nanoscale resolution is critical for investigating the spatial organization and interactions of cellular organelles and protein complexes. We present a super-resolution light microscope that enables simultaneous multicolor imaging of whole mammalian cells at ~20 nm 3D resolution. We show its power for cell biology research with fluorescence images that resolved the highly convoluted Golgi apparatus and the close contacts between the endoplasmic reticulum and the plasma membrane, structures that have traditionally been the imaging realm of electron microscopy.